Age Influences Microglial Activation After Cuprizone-Induced Demyelination - Klein, Barbara; Mrowetz, Heike; Barker, Conor Michael; Lange, Simona; Rivera, Francisco J.; Aigner, Ludwig (Frontiers in Aging Neuroscience, 2018)
Multiple sclerosis (MS) is a chronic inflammatory CNS disease, which causes demyelinated lesions and damages white and grey matter regions. Ageing is an important factor in the progression of MS, and microglia, the immune cells of the CNS tissue, play an important role in all disease stages. During ageing, microglia are functionally altered. These age-related changes probably already begin early and might influence the progression of CNS pathologies. The aim of the present study was to analyze whether microglia in the middle-aged CNS already react differently to demyelination. For this purpose, several microglia markers (Iba-1, P2RY12, F4/80, CD68, MHCII, Marco, TSPO, CD206, CD163) were analyzed in the acute cuprizone demyelination model in young (2-months-old) and middle-aged (10-months-old) mice. In addition, microglial proliferation was quantified using double-labelling with PCNA and BrdU, which was injected with the onset of remyelination. To compare age-related microglial changes during de- and remyelination in both grey and white matter, the hilus of the dorsal hippocampal dentate gyrus and the splenium of the corpus callosum were analyzed in parallel. Age-related changes in microglia of the healthy controls were more pronounced in the analyzed grey matter region (higher levels of F4/80 and Marco as well as lower expression of CD68 and MHCII in middle-aged mice). During de- and remyelination, a stronger induction of the microglial markers Iba-1, CD68, and TSPO was observed in the splenium of the younger groups than in the middle-aged ones. There was a significant reduction of P2RY12 during demyelination, however, this was age- and region-dependent. The induction of the anti-inflammatory markers CD206 and CD163 was more pronounced in the middle-aged group, but also differed between the two analyzed regions. De- and remyelination induced a significant increase in PCNA+ microglia only in the young group within the white matter region. The number of BrdU+ microglia was not changed during de- or remyelination. These results clearly show that microglia are already altered during middle-age and also react differently to CNS demyelination, however, this is highly region-dependent.